Upaya Peningkatan Partisipasi Masyarakat dalam Pencegahan Penularan Covid-19 dan Optimalisasi Adaptasi Kebiasaan Baru - Alfaina Wahyuni; Rahmalika Fitri; M Zulfani Najmi; Della Lovy; M. Rafif Rafif; Afifatul Latifah (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Since the start of the pandemic, the number of positive COVID-19 cases in DIY has been steadily increasing. This includes the Kasihan 2 Health Center in Bantul's work area. UMY Thematic Health KKN students identified several Covid-19-related issues. Based on the root cause analysis, four programs have been identified: (1) IT-based assistance and monitoring programs for COVID-19 survivors, (2) comorbid screening programs for the elderly population, (3) mentoring programs for COVID-19 survivors who have recovered, and (4) Covid-19 transmission prevention programs, vaccinations, and the implementation of new adaptations for health cadres and community volunteers. With this activity, it is hoped that patients will be able to live a happy isolation period, without appearing to be isolated and feeling cared for, so that immunity can be maintained and healed without sequelae, there is an increase in the knowledge of post-recovery patients so that they do not become infected again, and they can also become reliable educators and motivators for other communities. , the gathering of information on the elderly with comorbidities. Furthermore, it is hoped that by optimizing the empowerment of health cadres and community volunteers, public awareness of the importance of adhering to health protocols during the new life during the COVID-19 pandemic will increase. Door-to-door comorbid screening activities cannot be carried out optimally because, according to the Covid-19 task force, they are too dangerous for students. In general, all activities went off without a hitch, with nearly 100% participation.